Reverse‐flow latissimus dorsi myocutaneous flap in a multi‐step approach for complex back defect reconstruction: A case report. Issue 5 (4th June 2020) - Menichini, Giulio; Lucattelli, Elena; Innocenti, Alessandro; Brogi, Mattia; Cipriani, Federico; Innocenti, Marco
Abstract: Reconstruction of complex back defects is challenging for reconstructive surgeons, as it should preserve function, provide adequate coverage, and minimize morbidity. We present a case of multiple‐step reconstruction after resection of a large squamous cell carcinoma recurrence in a 68‐year‐old man, with local perforator flaps and a reverse‐flow latissimus dorsi myocutaneous flap. After radical excision, four propeller perforator flaps were harvested to cover a 30 × 25 cm defect, based on the dorsal branch of the fifth posterior intercostal arteries (right 20 × 9 cm, left 17 × 9 cm) and on the superior gluteal arteries (right 20 × 11 cm, left 21 × 12 cm) bilaterally. In the second step, bilateral propeller perforator flaps based on the fourth lumbar arteries (right 18 × 13 cm, left 23 × 11 cm) were transposed to cover the residual loss of tissues. After 5 months, a recurrence occurred on the left midback. A wide en bloc excision of the last three ribs and pulmonary pleura was performed, and the synthetic mesh used for thoracic wall reconstruction was covered with an ipsilateral 20 × 10 cm reverse‐flow latissimus dorsi myocutaneous flap based on the serratus anterior branch. All the flaps healed uneventfully and there were no donor‐site complications. Two years postoperatively, the patient had a cosmetically acceptable result without any functional impairment. The reverse‐flow latissimus dorsi myocutaneous flap can represent a salvage procedure in back complex defects reconstruction, especially when other local flaps have already been harvested in previous reconstructive procedures.